Eloquence Assemblage in Andalusian Poetry - جنان قحطان فرحان (College of Education for Women, 2019)
The eloquence assemblage, as it is appeared in this research, is the most prominent terms that accompany the art. It includes the whole artworkand it does not stop at the borders of the construction, but also extends to the material presented in this or that work. It means the discovery of all that essential in the material presented and it is far away from what is accidental and fleeting. Moreover, it is the type of pressure of the poetic status and the familiarity with the material flowing subconsciously. It means that the clever poet masters his language alongside with his discernment and intelligence framed by fast-witted. The semantic assemblage within the technical construction means focusing on what embodies that material and it suggests it and expresses it and gets rid of everything that is redundant, such as extra explanation and details and every thing that has relationship with disability of the art work effectiveness. The eloquence assemblage includes the technical image as the image is a spatial and temporal forms that includes a brief process where no place but for the essentials to represent a distinct and unique linguistic and stylistics economic. The eloquence assemblage makes the text opened to interpretation, especially when it becomes a source for the mysterious and suggested symbols and signs assemblaged within the framework of the technical picture and what metaphor, allegory and simile it has and it plays an important role in enriching the semantic meaning. In fact this depends on the poet's ability and the speed of his picking all that is striking and influential and summarizes his artistic work in the overall equation similar to the chemical equation. The researcher discusses the eloquence assemblage in several axes and as followings: - words assemblage linguistically and idiomatically - pressure of words and its semantic interpretation - Mystery and its suggestive connotations - Clarity and its creative and technical connotations - eloquence mobilization and its artistic continuous. At the end, the research puts a list of references and sources and the abstract in English.